Research on preparation and flame retardancy of melamine-modified flame retardant loofah composites. (30th June 2022) - Pan, Mengli; Chen, Weijia; Dai, Jing; Shu, Zhongjun; Xue, Honglai; Xu, Jiacheng; Ou, Hongxiang
As a natural plant material with unique porous structure, loofah is used in many fields, but there are still defects in fire safety performance in that its flammability. The melamine-modified flame retardant loofah composites (M-FR-PL) were prepared by impregnation baking method. The experimental synthesis conditions were optimized by L9 (3 4 ) orthogonal design. The flame retardancy, heat release rate (HRR), thermal stability and smoke density of the composites were analyzed. M-FR-PL6 prepared under the optimum experimental conditions had good properties: the adsorption rate of flame retardant (AR, %) was 6.8%, the limiting oxygen index (LOI, %) reached 27.5%, the vertical combustion level reached V-0, and the amount of residual char was 17.2% higher than that of loofah. The flame retardant mechanism of M-FR-PL6 was thoroughly discussed by various characterization methods. The peak of the HRR curve of M-FR-PL6 declined compared with loofah, indicating the loofah after melamine flame-retardant treatment has good flame retardancy and smoke suppression properties.